The Factors That Influence Mothers To Provide Exclusive Breastfeeding For Babies Aged 0-6 Months At The Becora Community Health Center In Dili, In 2023 - Oqui, Maximiano; Bartolomeu Freitas, Isabel; Evaristo Obeno, Olandino; Julieta Geri de Sena Amaral, Saturnina; Freitas Moreira, Adriano; Deonisio Ximenes, Jose; Francisco da Cunha Cardoso, Gilton (CV RIFAINSTITUT, 2024)
The lactation period is a natural process that occurs in mothers who have already given birth. During this period, it is not easy for mothers, as they need to have good knowledge in the process of providing exclusive breastfeeding. The high-quality protein and nutrition in maternal milk are crucial for providing newborn babies aged 0-6 months. According to data from the Ministry of Health (MoH), the prevalence of mothers who provide exclusive breastfeeding to their babies during the first few months decreased from 62.3% in 2013 to 50.2% in 2016, then increased to 64.2% in 2020. Meanwhile, the prevalence of babies consuming formula milk decreased from 50% in 2016 to 32.1% in 2020. This research aims to identify the factors influencing mothers to provide exclusive breastfeeding to babies aged 0-6 months at the Becora Community Health Center in Dili, in the year 2023. The researcher employs an analytical quantitative method with a cross-sectional study approach for this research. The bivariate analysis results show an influence between knowledge and the provision of exclusive breastfeeding based on the Chi-Square statistical analysis with a p-value of 0.00<0.05, and the Kendall's tau-b analysis indicates a result of 0.69, suggesting a strong influence between maternal knowledge and the provision of exclusive breastfeeding to babies. The Chi-Square statistical analysis results between maternal attitude and the provision of exclusive breastfeeding indicate a p-value of 0.05<0.05, and the contingency coefficient analysis shows a result of 0.21, suggesting a weaker influence between maternal attitude and the provision of exclusive breastfeeding. There is a strong influence between maternal knowledge and the provision of exclusive breastfeeding, and there is also a weaker influence between maternal attitude and the provision of exclusive breastfeeding.